EVALUASI KINERJA KOPERASI DENGAN METODE BALANCED SCORECARD TERHADAP KOPERASI KELUARGA BESAR IKOPIN - windayani windayani (COMPETITIVE, 2022)
This study aims to determine how the perfomance of Koperasi Keluarga Besar (KKB) Ikopin in Sumedang Jatinangor, in this study it is viewed from the balanced scorecard, namely by looking at the financial perspective, customer perspective, and learning and growth perspective. In this research, it was carried out from March to April 2021. The data used are quantitative data, with primary and secondary data sources that exist in the Koperasi Keluarga Besar (KKB) Ikopin with a total sample of 18 member respondents, in data analysis used Balanced Scorecard method which is an analysis of financial perspective, customer perspective, and learning and growth perspective. And the results of the study indicate that the performance of Koperasi Keluarga Besar (KKB) Ikopin using the balanced scorecard method wich is a financial, a customer perspective, as well as a learning and growth perspective is considered quite good and satisfactory, the customer perspective is considered quite good and satisfactory, and the financial perspective is considered satisfactory. Not good because it is below the standard average value.